2010
DOI: 10.1074/jbc.m109.093880
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D Controls Actin Polymerization and Cell Motility through Phosphorylation of Cortactin

Abstract: We here identify protein kinase D (PKD) as an upstream regulator of the F-actin-binding protein cortactin and the Arp actin polymerization machinery. PKD phosphorylates cortactin in vitro and in vivo at serine 298 thereby generating a 14-3-3 binding motif. In vitro, a phosphorylation-deficient cortactin-S298A protein accelerated VCA-Arp-cortactin-mediated synergistic actin polymerization and showed reduced F-actin binding, indicative of enhanced turnover of nucleation complexes. In vivo, cortactin co-localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 38 publications
(77 reference statements)
5
121
0
Order By: Relevance
“…At the Golgi complex, PKD regulates vesicular traffic to the plasma membrane, whereas at the plasma membrane PKD is involved in the regulation of cell shape, movement, and invasion. In line with such functions, substrates associated with actin cytoskeletal remodeling including cortactin, DLC1, RIN1, SSH1L, and Pak4 were recently identified to be phosphorylated by PKD (21)(22)(23)(24)(25)(26). Most of these studies focused on PKD1 and/or PKD2 isoforms, whereas relatively little is known about PKD3.…”
Section: G-protein Coupled Receptor Kinase-interacting Protein 1 (Git1)mentioning
confidence: 99%
“…At the Golgi complex, PKD regulates vesicular traffic to the plasma membrane, whereas at the plasma membrane PKD is involved in the regulation of cell shape, movement, and invasion. In line with such functions, substrates associated with actin cytoskeletal remodeling including cortactin, DLC1, RIN1, SSH1L, and Pak4 were recently identified to be phosphorylated by PKD (21)(22)(23)(24)(25)(26). Most of these studies focused on PKD1 and/or PKD2 isoforms, whereas relatively little is known about PKD3.…”
Section: G-protein Coupled Receptor Kinase-interacting Protein 1 (Git1)mentioning
confidence: 99%
“…This may be an important goal for future therapeutics as there is emerging evidence that PKD isoforms play different roles in tumors of different origin. For example, a series of studies by Eiseler and coworkers found that PKD1 negatively regulates migration of Panc89 cells through several related mechanisms including association of PKD with F-actin and phosphorylation of cortactin and slingshot 1 (SSH1) (42)(43)(44). In addition, PKD1 expression is decreased in invasive breast cancers and expression of a constitutively active PKD1 mutant decreased the invasiveness of MDA-MB-231 breast carcinoma cells by causing a subsequent decrease in matrix metalloproteinase expression (45).…”
Section: Pkd and Tumor Angiogenesismentioning
confidence: 99%
“…We tested whether cortactin was a direct substrate for aPKCζ/ι by incubating purified GST-tagged human cortactin in the presence of recombinant human aPKCι. Phosphorylation was detected with antibodies raised against cortactin phosphoSer298, which was recently identified as a phosphorylation site for aPKCζ/ι-related PKD (35,36). In higher metazoans, mRNA splicing generates cortactin variants with four, five, or six conserved tandem actin-binding repeats in which repeats 5 and 6 are the most conserved (37).…”
Section: Apkcζ/ι-dependent Phosphorylation Of Cortactin Controls Itsmentioning
confidence: 99%